Workload, Work Environment, Organizational Culture and Its Influence on the Performance of Indonesian Migrant Workers in Koperasi Ladang Berhad, Terengganu - Awa Awa; Erni Yuningsih; Yoyok Priyo Hutomo; Lia Kian; M. Albi Sahal Ma’hadi; Fina Aprilia; Karmila Karmila; Alisya Subhani; Tiara Cahyani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Companies in Malaysia employ a significant number of Indonesian workers, such as cooperatives, which play a crucial role in the palm oil business in Malaysia. Cooperatives are also growing, particularly in the palm oil plantation and farming sectors. However, Indonesian migrant workers' performance is still suboptimal. Factors that contribute to worker performance need to be addressed as a means of improvement. Comprehensive research on the influence of workload, work environment, and organizational culture on worker performance of Indonesian Migrant Workers in Malaysia, with a case study of cooperatives, namely Indonesian Migrant Workers at Koperasi Ladang Berhad, Terengganu involving all of these variables has not been studied before. This study examines the effects of workload, work environment, and organizational culture on the performance of Indonesian migrant workers at Koperasi Ladang Berhad, Terengganu. A quantitative approach was employed, utilizing a saturated sampling technique through the distribution of questionnaires to all 68 Indonesian migrant workers at the organization. Researchers used multiple linear regression data analysis with data tabulation through SPSS 27. The study found that, individually, workload has a negative and significant effect on worker performance, while both work environment and organizational culture have positive and significant effects. Collectively, workload, work environment, and organizational culture significantly influence worker performance. The coefficient of determination indicates that 91.4% of the variance in worker performance can be explained by these three variables, with the remaining 8.6% attributable to factors outside the research model. These findings may serve as a reference for researchers, business practitioners, and stakeholders, and further research in other sectors is recommended.